Pelatihan dan Job Desk terhadap Loyalitas Kerja Karyawan - Anasthasia Pricillia Handayani; Syawaluddin Syawaluddin; Mila Asmawiani Okta; Thomas Sumarsan Goh (IPM2KPE, 2022)
This study aims to determine the effect of training and job desk on employee loyalty at PT. Prosperity Mainstay of Palm Oil. This research method is descriptive quantitative. The total population in the study was 75 employees with a sampling technique using saturated samples. Data analysis used descriptive statistics and multiple linear regression. The results showed that simultaneously there was a significant influence between the training and job desk variables on employee loyalty at PT. Prosperity Mainstay of Palm Oil. While partially the variables found that training has a significant effect on employee loyalty at PT. Prosperity Mainstay of Palm Oil. Partially, it was found that the job desk variable had a significant effect on employee loyalty at PT. Prosperity Mainstay of Palm Oil. In conclusion, the job desk variable has more influence than training on employee loyalty at PT. Prosperity Mainstay of Palm Oil. Keywords: Job desk, Job Loyalty, Training